The Role Of Endothelial Nitric Oxide Synthase (Enos) Gene Glu298asp Polymorphism In Postmenopausal Coronary Artery Disease Risk- A Pilot Study In North India - PRADEEP K. DABLA; SHUBHA S. TRIVEDI; NIBHRITI DAS; JAYASHREE BHATTACHARJEE (International Journal of Pharma and Bio Sciences, 2010)
This study evaluates the endothelial dysfunction in postmenopausal women in relation to eNOS Glu298Asp gene polymorphism and its effect on other proatherosclerotic markers to increase CAD risk.Fifty postmenopausal women were compared with fifty premenopausal women in 45-55 years of age group. We studied eNOS Glu298Asp gene polymorphism and estimated different cardiac risk parameters: nitric oxide, malondialdehyde, platelet factor-4, estriol and lipids. The postmenopausal women had significantly low estriol and low NO levels whereas triglyceride levels were high (p<0.001) compared to premenopausal women. The NO level found to be significantly lower (<0.05) whereas PF4 and MDA have shown significant higher (p<0.001) levels in GT genotype. These observations suggest that eNOS Glu298Asp gene polymorphism and thus, low NO levels may increase the association of future CAD risk in postmenopausal women. However, further studies and follow up of the patients are required to improve the therapeutic strategies.